Optimal planning and operation approach for the multi-terminal MMC-HVDC transmission system - Phoa, Jun Xiong (Nanyang Technological University, 2021)
This report is focusing on Multi-Terminal Modular Multilevel Converter – High Voltage Direct Current (MMC-HVDC) transmission system. This transmission system helps to integrate renewable energy sources such as solar panel and wind turbine into the power grid. Most of the traditional power grid uses combustion of fossil fuel to produce energy and transmit it to the generator. However, combustion of fossil fuel may lead to global warming and air pollution, which are harmful to the earth and human beings. Hence, there are countries, like United States and China, moving towards renewable energy sources to reduce the rate of global warming. The objective of this project is to come up with an optimization model for MMC-HVDC transmission system, as well as to investigate the costs of operation. Moving on from there, the author needs to analyze minimal cost of operation with adequate power efficiency. The transmission system structure of Zhoushan island in China will be used as an optimization model in this project. There are two strategies in this project, which are the operation and planning of the transmission system that will be further elaborate in the later part of the report. The results are analyzed in graphical chart to compare for the most effective cost of operation. High level programming such as MATLAB, YALMIP and GUROBI are used in the optimization model.